Les écarts de revenus dans les espaces transfrontaliers. Des moteurs de la mobilité transfrontalière - Belkacem, Rachid (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „This article analyses wage disparity in cross-border spaces in the Greater Region (GR) and Upper Rhine. It is based on the results of two studies, the first funded by EURopean Employment Services-Greater Region (EURES-GR) in 2022 and the other, ongoing, funded by EURopean Employment Services-T Upper Rhine. The analysis shows that this disparity can be explained by various economic, sociological and institutional factors, which operate on various levels: micro (relating to corporate policies), macro (relating to national taxation and social security policy) and meso (relating to economic sectors and branches). It begins by showing that salaries and their various component parts are hard to define, making cross-border comparison difficult. It then signals that while wages in Switzerland and Luxembourg are very attractive, they must be balanced against the cost of living and working hours, which differ on each side of the border. The main takeaway from this analysis is that the gap between wages and the cost of living is a significant driver of cross-border working in border regions.“
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lohnniveau; Mobilität; Schweiz; Wohnen; Wohnungsmarkt

Introduction. Cross-Border Inequalities. An Exploration in the Greater Region - Connor, Ulla; Aubry, Lola (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Mobilität; Wohnen; Wohnungsmarkt

Border-Crossing and “Temporal Otherness” in the Greater Region SaarLorLux. Residential Migrants’ Experiences of Divergence - Boesen, Elisabeth (Borders in Globalization Review, 2024)
Abstract: „This article deals with border-crossing and the experiences of “temporal otherness” of residential migrants who move their home from Luxembourg to the German side of the River Moselle. Research on temporal borders is highly influenced by a particular spatio-political relation: the West creating its underdeveloped other and coping with this other by controlling border-crossing, which in turn results in maintaining the idea of the other’s temporal remoteness. The Luxembourgish–German border region offers a complement to this perspective; here, one encounters migrants who move in the opposite temporal direction and appreciate certain forms of “being behind” in their new place of residence. These migrants must cope with divergences, i.e., with the fact that economic and socio-cultural conditions within their new socio-spatial universe, the cross-border region, have evolved differently. This article argues that the analysis of migrants’ memories is illuminating with respect to the question of the moral legitimacy of moving, and thus regarding the conception and everyday construction of cross-border communities. It sheds light on the fact that borderland research—by focusing on national differences and related conceptions of cross-border mobility and exchange—tends to ignore borderlanders’ notions of (regional) unity and related claims for convergence.“
Keywords: Fremdheit; Grenzarbeitnehmer; Mobilität; Sozialraum

„Die schlechten Straßen unter seinen Füßen“. Die Entwicklung der Mobilität der deutschsprachigen Belgier zwischen 1973 und 2023 - Sproten, Vitus (Föderalisierung, Strukturwandel, Erwartungshorizonte (1973–heute), 2023)
Keywords: Mobilität; Verkehr

„Für uns ist die grenzüberschreitende Zusammenarbeit eine Selbstverständlichkeit ...“ Die Großregion SaarLorLux aus Sicht von Kulturakteuren - Sonntag, Monika (Lebenswirklichkeiten und politische Konstruktionen in Grenzregionen. Das Beispiel der Großregion SaaLorLux. Wirtschaft – Politik – Alltag – Kultur, 2015)
Abstract: „Kulturpolitische Vereinbarungen der Großregion SaarLorLux enthalten das Ziel, durch die Förderung der grenzüberschreitenden Mobilität von Kulturschaffenden und des Publikums einen gemeinsamen »Lebens- und Kulturraum« zu schaffen. Der Beitrag beantwortet die Frage, wie einzelne Akteursgruppen des Kulturbereichs die Großregion SaarLorLux als Handlungsraum erleben und beschreiben. Im Mittelpunkt steht die Perspektive zweier Akteursgruppen, die in ihrem Berufsalltag grenzüberschreitend tätig sind und somit diesen Raum aktiv mitgestalten. Dies sind zum einen Mitarbeiter der regionalen Kulturministerien, die mit der Koordination und Ausgestaltung grenzüberschreitender Kulturförderprogramme betraut sind. Aus ihrer Sicht stellt sich die Großregion SaarLorLux als Mosaik unterschiedlich stark kulturpolitisch engagierter Teilregionen dar. Zum anderen kommen Kulturschaffende des Museumsbereichs zu Wort, die in grenzüberschreitende Projekte eingebunden sind. Dabei zeigt sich, dass sie die Zusammenarbeit mit internationalen Partnern als Selbstverständlichkeit und Notwendigkeit für die eigene Kreativität und künstlerische Tätigkeit betrachten. Je nach Arbeitskontext gehen ihre Kooperationsnetzwerke auch über die Großregion SaarLorLux hinaus. Allerdings richten sich die einzelnen Museen und Kulturinstitutionen an jeweils unterschiedliche Zielgruppen, die nicht alle gleichermaßen grenzüberschreitend mobil sind. Bei genauerer Betrachtung stehen der räumlichen Mobilität des Publikums in erster Linie soziale Grenzen im Hinblick auf den Zugang zu Bildung und Kultur im Wege. Die kulturpolitische Gestaltung der Großregion SaarLorLux als Lebenswirklichkeit für verschiedene Akteurs- und Bevölkerungsgruppen im Kulturbereich sollte daher die vorhandenen sozialräumlichen Disparitäten und Grenzen stärker berücksichtigen.“
Keywords: Grenzüberschreitende Kooperation; Kulturelle Kooperation; Kulturpolitik; Mobilität; Museum

Impacts de la mobilité résidentielle transfrontalière sur les espaces de la vie quotidienne des actifs du Luxembourg - Gerber, Philippe; Carpentier-Postel, Samuel (Economie et Statistique, 2012)
Abstract: „À partir d'une enquête effectuée par le CEPS/INSTEAD et la fondation Forum Europa, cet article analyse le phénomène de mobilité résidentielle transfrontalière et son impact sur les déplacements quotidiens. Réalisée au printemps 2008, cette enquête porte sur les actifs occupés résidant initialement au Luxembourg qui se sont installés dans un pays frontalier entre 2001 et 2007, tout en conservant leur emploi au Grand-Duché. Pour un grand nombre d'entre eux, le déménagement transfrontalier a permis d'accéder à un logement plus grand, voire d'en devenir propriétaire. Néanmoins, l'analyse des déplacements quotidiens montre que la grande majorité de ces personnes a dû consentir à de nombreuses concessions en termes de mobilité pour accéder au logement souhaité. Cela se ressent particulièrement pour le trajet domicile/travail dont la distance moyenne a doublé, ce qui a renforcé la dépendance des personnes concernées vis-à-vis de l'automobile. En dehors même du travail, la localisation des autres activités quotidiennes se trouve modifiée à la suite du déménagement. Des indicateurs synthétiques issus de la géostatistique permettent d'analyser la reconfiguration des lieux de ces activités. Malgré la relocalisation de beaucoup d'entre elles autour du nouveau lieu de résidence, une certaine inertie des comportements se traduit par le maintien de près d'une activité sur trois au Luxembourg. Dès lors, la dispersion des espaces d'activités augmente pour certains enquêtés. Cette dispersion, liée à la part des activités transférées vers le pays de résidence, varie fortement selon la nationalité; elle est plus forte pour les Luxembourgeois et pour les Portugais. Les personnes originaires des régions frontalières, qui retournent dans leur pays d'origine, gardent également près d'un quart de leurs activités au Grand-Duché: cela témoigne à la fois de l'importance du lieu de travail dans la structuration des espaces de vie quotidienne et d'un capital spatial déjà mis en évidence dans le cas d'actifs résidant au Luxembourg.“
Keywords: Grenzarbeitnehmer; Mobilität; Sozialraum; Wohnungsmarkt

La mobilité résidentielle transfrontalière entre le Luxembourg et ses régions voisines. Un panorama - Carpentier-Postel, Samuel; Gengler, Claude; Gerber, Philippe (Géo-Regards. Revue Neuchâteloise de Géographie, 2011)
Abstract: „L’article propose un panorama du phénomène de mobilité résidentielle transfrontalière entre le Luxembourg et ses régions voisines (Lorraine, Wallonie, Rhénanie-Palatinat, Sarre). Le pays voit en effet un nombre croissant de personnes actives le quitter pour s’installer de l’autre côté de la frontière, tout en continuant à travailler au Luxembourg. Les auteurs s’intéressent à l’ampleur du phénomène, aux lieux de départ et d’arrivée, aux motivations des partants et à d’autres facettes caractérisant ce type particulier de mobilité résidentielle.“
Keywords: Grenzarbeitnehmer; Mobilität

Zum Modell des transnationalen sozialen Raums im Kontext von Grenzregionen. Theoretisch-konzeptionelle Überlegungen am Beispiel des Grenzgängerwesens - Wille, Christian (Europa Regional, 2009)
Abstract: „Angesichts fortschreitender Globalisierung gewinnen übernationale Sozialbeziehungen zunehmend an Bedeutung. Sie rücken als Forschungsgegenstände immer stärker in die Human- und Sozialwissenschaften ein und stellen die teilweise noch an ‚verankerten’ Lebensbedingungen orientierten analytischen Konzepte in Frage. So ist teilweise ein Wandel weg von statischen, homogenisierenden und abgeschlossenen Modellen von Gesellschaft, Kultur und Raum hin zu entsprechend offenen und dynamischen Konzepten auszumachen. Diese können wichtige Impulse geben für Fragestellungen und ihre theoretischen Annäherungen auf der kleinräumigen Ebene von benachbarten Grenzregionen. Im vorliegenden Beitrag soll hierfür das Modell des transnationalen sozialen Raums aufgegriffen und im Hinblick auf grenzüberschreitende Sozialverflechtungen zwischen europäischen Grenzregionen theoretisch-konzeptionell diskutiert werden. Dafür werden zunächst die Mobilitätstypen des Transmigranten und des Grenzgängers erläutert und auf empirischer Ebene beispielhaft Bezüge zu einer bei Grenzgängern in der „Großregion SaarLorLux“ durchgeführten Studie hergestellt. Das im Umfeld der Migrationsforschung entwickelte und vorzustellende Modell fokussiert auf dauerhafte Sozialzusammenhänge, die über Nationalstaaten hinausreichen und neue Vergesellschaftungszusammenhänge konstituieren, gleichwohl bleibt es in seiner Konzeption und Analytik weitgehend einem statischen und nationalstaatlichen Denken verhaftet. Vor diesem Hintergrund wird versucht, die zentralen Desiderata und mögliche Entwicklungsperspektiven für die Erforschung transnationaler Sozialzusammenhänge in Grenzregionen herauszuarbeiten. Given the continuing processes of globalisation, social networks that can be categorised as being above the national level are coming to the fore. They are also making constant headway as research topics in the human and social sciences by calling analytical concepts into question that are still geared towards “rooted” life conditions. For instance, there is a move away from statistical, homogenising and closed models of society, culture and space to more open and dynamic concepts that can provide important motivation for questions and their way they theoretically approach these issues on the small-space level of neighbouring border regions. This article will address the model of a transnational social space and discuss it in the framework of cross-border social interconnections between European border regions. It will start off by explaining the types of mobility that transmigrants and cross-border commuters have and then empirically and exemplarily linking this to a study made on cross-border commuters in the large-scale SaarLorLux region. The model to be presented here has been developed in the context of migration research and it focuses on permanent social connections that go beyond national states and constitute new connections of socialisation, even though its conception and analytical methods mostly remain dedicated to static thinking and to the national state. Given these facts, this article attempts to outline the central desiderata and potential development vistas for the research on transnational social relationships in border regions.“
Keywords: Arbeitnehmer; Arbeitsmigration; Grenzarbeitnehmer; Mobilität; Pendler; Sozialraum; Transnationalisierung

Les pratiques commerciales dans une région frontalière. Les exemples d’Arlon, de Luxembourg-ville et de Metz - Smits, Florence (Belgeo, 2006)
Abstract: „Parts of Belgium, France, Germany and Luxembourg which comprise the Great Region have witnessed an increase in the mobility of workers and in the degree of political collaboration. Nevertheless, this evolution does not seem to have had an impact on the consumption habits of workers who tend to remain quite different in Arlon, Luxembourg and Metz. In contrast, people with less mobility but more time available, such as the retired and young, seem to exhibit the same pattern of consumption.“
Keywords: Arlon; Einkaufen; Grenzarbeitnehmer; Handel; Luxemburg (Stadt); Metz; Mobilität; Verbrauch